Development of fruit waste derived bio-adsorbents for wastewater treatment: A review - Solangi, Nadeem Hussain; Kumar, Jai; Mazari, Shaukat Ali; Ahmed, Shoaib; Fatima, Noor; Mubarak, Nabisab Mujawar (Journal of hazardous materials, 2021)
Hazardous contamination of water is a major hurdle in the provision of usable and drinkable water to the world. Innovative, economic, renewable and environment friendly technologies are need of the hour for wastewater treatment. Several technologies such as ion-exchange, co-precipitation, adsorption, membrane separation, oxidation, biochemical processes etc. are being researched to encourage the wastewater treatment. Among these technologies, the adsorption is being considered as a promising approach owing to its short route. To adsorb the pollutants, different types of adsorbents are synthesized and utilized for wastewater treatment. The bio-adsorbents (BAs) from waste biomass sources are renewable, sustainable, economical, and ecofriendly for wastewater treatment. Among other biomass waste sources, fruit-based biomass wastes are on rise due to global food and fruit demand. The utilization of fruit wastes for the development of BAs have received high attention due to their low cost, rich in bio cellulose and abundance. Herein, we report a comprehensive review on the fruit waste derived bio-adsorbents for wastewater treatment. The manuscript includes synthesis, characterizations, and utilization of fruit waste derived bio-adsorbents for removal of various water contaminants. Characteristics, adsorption capacities, isotherms and adsorption kinetics of various bio-adsorbents and influence of parameters on adsorption is provided and critically analyzed. [Display omitted] •Waste fruit derived bio-adsorbents are competing candidates for wastewater treatment.•Pseudo second order rate equation dominates adsorption kinetics using bio-adsorbents.•In several cases Langmuir isotherm better fits the adsorption behavior.•Fruit waste utilization can bridge water-energy-food nexus gap.•Challenges on commercialization of fruit waste derived bio-adsorbents need to be addressed.